The East Asia security environment in the beginning of the twenty-first century and the adjustments in Vietnamese foreign policy - Pham, Quang Minh (Asia-Pacific Review, 2019)
International relations are social actions, and their expression is behavior of the states. According to French sociologist Pierre Bourdieu, the basis for any social action is habitus and capital (Bourdieu 1982). For Bourdieu, social action is not created in a vacuum but always takes place under certain social conditions. Different social conditions create different spheres that Bourdieu called action fields. The problem is that each field has its own rules, logic and goals. Bourdieu also uses the metaphor of game to explain the concept of field. Like the fields each game has also its own rules and logic. In order to participate in the game players are required to have some knowledge of game, and capacity, skills, and last but not least the interests to play game. The field of the Asia-Pacific region in the beginning of twenty-first century and especially during recent years is one of “center court” of the whole world involving all big players like the US, China, Japan, Russia and India. Their presence with their own behavior and different abilities, interests make this field more interesting, but at the same time more complicated and unpredictable. This article explores the different phases of Vietnam’s foreign policy since reform in 1986 and joining ASEAN and adoption of “Resolution No. 8 (section IX) on the Strategy for Fatherland Defence in the New Context” in 1995